Why Track 2 MAiD is Discriminatory - Grant, Isabel (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
This paper argues that Canada’s Track 2 Medical Assistance in Dying (MAiD) regime is discriminatory against people with disabilities, and has a disproportionate impact on women with disabilities. It is important to expose critical gaps in pro-MAiD advocacy, which obscures how systemic marginalization shapes access to assisted death. Premised on a medical model of disability which exceptionalizes disability-related suffering as uniquely intolerable, Track 2 MAiD poses heightened risks for those already disadvantaged by structural inequalities. By framing death as a medical treatment, the law reinforces ableist assumptions that portray people with disabilities as better off dead instead of providing access to essential supports. These social inequalities are heightened for disabled women who experience alarming rates of male violence, the intersection of medical ableism and sexism, as well as the assumption that women should be caregivers and not those needing care.